Anti-Cancer Nanomedicines: A Revolution of Tumor Immunotherapy - Li, Wei; Peng, Anghui; Wu, Huajun; Quan, Yingyao; Li, Yong; Lu, Ligong; Cui, Min (Frontiers in Immunology, 2020)
Immunotherapies have been accelerating the development in anti-cancer clinical treatment, however, the low objective responses and severe off-target immune-related adverse events (irAEs) limit their widely application. Strategies to remove these obstacles primarily focus on the combination with different therapies and the exploitation of new immunotherapeutic agents. Nanomedicine offers distinctive perspectives in imaging diagnosis and tumor treatment. Nanomedicine potentiates the effects of activating immune cell selectively and reverses tumor induced immune deficiency microenvironment through multiple mechanisms in tumor immunotherapy. In the last decade, variety of nano-enabled tumor immunotherapy treatments is under clinical investigation. In this Review, we wish to provide an overview of the progression and challenges of tumor immunotherapy and the mechanisms that nanomaterials under development or in the clinic that aim to enhance the efficacy of tumor immunotherapy.